Modalities of training parameter alternation in nowadays strength training practice - Ranisavljev, I.; Ilic, V. (Journal of Physical Education and Sport, 2010)
Large number of variables could be alternated during the process of planning and programming in sports training. Superior training results in majority of sports are achieved by optimally manipulating training parameters in appropriate sequences and combinations. Additionally, in some sports they might be the result of appropriate periodization pattern. Today's tendency in strength training practice is training movements instead of training muscles. Exercise classification according to the dominant movement types, allows creating new modalities in training alternation. Additional variations in volume, intensity, rest brakes, repetition velocity and inter-repetition rest can be the important part of functional strength training program. Alternation and combination of different training parameters makes appropriate training stimulus for strength increase in the most of nowadays sports. Optimal alternation of basic training parameters should be the first part in the process of planning and programming. As a result, majority of athletes might not need advanced periodization patterns for optimal improvement in muscle strength and power.